PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 DASAR DAN TUJUAN YANG RELEVAN PERSPEKTIF AL-QURAN DAN HADIS - Fadil, Muhammad Ikhsan (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The advent of the Society 5.0 era not only opens up new opportunities to achieve greater effectiveness and inclusivity in education but also presents various challenges. To create a resilient generation ready to face these challenges, it is essential to establish the right educational foundation and goals for the generations that will be part of this Society 5.0. This paper aims to analyze the foundations and formulate Islamic educational goals contained in the Quran and Hadith, identifying ways in which Islamic education can be integrated into the Society 5.0 era while upholding strong Islamic principles. This research is a literature review, using a text analysis approach to the Quran and Hadith and literature studies. The results of this study indicate that the educational foundation derived from the Quran and Hadith formulates Islamic educational goals encompassing three main objectives. First, instilling faith and piety in Allah. Second, surrendering oneself to Allah, formulated into three parts: understanding the essence of life as a caliph and servant of Allah, developing knowledge, technology, and self-potential, and maintaining noble character (the concept of the integration of knowledge). Third, attaining happiness in both this world and the hereafter. With this formulation of educational goals, it is expected that learners will be able to navigate the complexities and challenges in the modern Society 5.0's society and technology dynamics.